Local Content Development for Targeted Group in Community Center - Abdul Hapes, Mohammed (2010)
Telecenter or community center is a place where it provides an opportunity for those who really in need the exposure to the ICT world. Telcenters has already contributed a lot in guiding and giving training so the people can make use of all the facilities provided. Despite that, by only providing the access to the net and the facilities is still not adequate to help them and make hem utilize the telecenter. So the telecenter administrators need to identify what are the contents to be offered that can magnetize the targeted group. If the contents able to attract them, so it is possible the targeted group especially for those who live in rural area be capable of compete with other groups of society in utilizing all the technologies facilities for the benefits of all the peoples.